2022
DOI: 10.3390/ijms231810294
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Activates Human Eosinophils via H2R and H4R Predominantly in Atopic Dermatitis Patients

Abstract: Atopic dermatitis (AD) is maintained by a variety of cells and inflammatory mediators, including eosinophils and histamine. We recently reported that eosinophils from AD patients highly express the H4R. However, its immunomodulatory function in eosinophils is still largely unexplored. In this study, transcriptome analysis of blood eosinophils from AD patients stimulated with histamine and the H4R agonist ST-1006 revealed several regulated genes (e.g., IL-18R, IL-1RL1, PDE4B, CXCR4) involved in inflammation. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[31][32][33] Furthermore an upregulation of IL-18 expression and its cognate receptor IL-18Rα was shown to be induced via H 2 -and H 4 -receptor in human eosinophils. 34 Altogether, these inspiring data demonstrate the significance of H 4 receptor in the regulation of several immune responses.…”
Section: The Stimulation Of H 4 Receptor Results In Increased Il-5 An...mentioning
confidence: 89%
See 1 more Smart Citation
“…[31][32][33] Furthermore an upregulation of IL-18 expression and its cognate receptor IL-18Rα was shown to be induced via H 2 -and H 4 -receptor in human eosinophils. 34 Altogether, these inspiring data demonstrate the significance of H 4 receptor in the regulation of several immune responses.…”
Section: The Stimulation Of H 4 Receptor Results In Increased Il-5 An...mentioning
confidence: 89%
“…Furthermore an upregulation of IL‐18 expression and its cognate receptor IL‐18Rα was shown to be induced via H 2 ‐ and H 4 ‐receptor in human eosinophils 34 …”
Section: Discussionmentioning
confidence: 97%
“…At the site of in ammation, eosinophils come into contact with histamine, which is mostly released from activated mast cells and basophils, resulting in strongly elevated levels of this bioamine in the skin of AD patients [21]. Eosinophils can be used as antigen presenting cells and Th-secreting cell chemokines to participate in obtaining immune responses, and can also be used as main effector cells to mediate tissue damage and functional disorders by releasing toxic particles and mitochondrial DNA [22].…”
Section: Resultsmentioning
confidence: 99%
“…Research by Beyer et al has shown that histamine and IFN-γ can synergistically upregulate the expression of IL-18R1 in eosinophils of AD patients. This promotive effect on IL-18R1 expression could lead to an increase in the expression of the eosinophil granule proteins [ 39 ]. Although in our study, only IL-18R1 was found to mediate the effect of plasma lipids on AD risk, part of our results indicates a significant correlation between plasma lipids and circulating inflammatory protein levels.…”
Section: Discussionmentioning
confidence: 99%